2012
DOI: 10.1097/olq.0b013e31823e68fe
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bacterial Vaginosis in Users of the Intrauterine Device

Abstract: BACKGROUND Users of the intrauterine device(IUD) may be at increased risk for bacterial vaginosis (BV). Our objective was to compare the incidence of BV in women using the IUD compared to women using combined oral contraceptives (COC), the contraceptive vaginal ring, and the contraceptive patch. METHODS We prospectively recruited women negative for BV at baseline. Monthly, for six months, participants returned a self-obtained vaginal smear for Gram stain by mail. BV was diagnosed by a Nugent score ≥7. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 24 publications
6
47
0
2
Order By: Relevance
“…41 and USA. 42 Our data supports the hypothesis that IUCD might change endogenous cervico-vaginal environment, which may lead to vulvovaginal infection and BV.…”
Section: Discussionsupporting
confidence: 78%
“…41 and USA. 42 Our data supports the hypothesis that IUCD might change endogenous cervico-vaginal environment, which may lead to vulvovaginal infection and BV.…”
Section: Discussionsupporting
confidence: 78%
“…This observation agrees with Lessard et al, [31], who did not find any increase in risk for acquiring BV by using IUD. But disagrees with Donders et al, [32] & Madden et al, [33] who have shown an increase in the risk of BV among IUD users. Also our finding disagrees with studies [26,34], that reported a protective effect of hormonal contraceptives against BV.…”
Section: Discussionmentioning
confidence: 42%
“…However, there is still no accurate explanation of their effect on the vaginal microbiota. Tessa Madden et al showed that the incidence of bacterial vaginosis is higher in IUD users than in women using other methods and detected a positive association with two mediators: the irregular vaginal bleeding and an intermediate vaginal microbiota (BVS III) present at implantation of the device [15]. In this study, the use of male condoms, a method chosen mainly by the security offered both contraception and sexually transmitted infections, was associated with an increase in the vaginal content with VIR.…”
Section: Discussionmentioning
confidence: 58%